Corrected likelihood ratio test statistics for a class of beta regressions with parametric link function - OLIVEIRA, Cristine Rauber (2020)
OLIVEIRA, Cristine Rauber, também é conhecido(a) em citações bibliográficas por: RAUBER, Cristine.